Proline rich regions of coenzyme A synthase α and β interact with SH3 domains of signaling proteins in vitro - Breus, O.S.; Panasyuk, G.G.; Gout, I.T.; Filonenko, V.V.; Nemazanyy, I.O. (Біополімери і клітина, 2008)
Coenzyme A-synthases α and β (CoASy α and CoASy β ) contain proline rich regions which may bring them into complexes with SH3-domain containing proteins. To test whether CoASy isoforms can bind to SH3 domains we performed in vitro pull down experiments. It was found that CoASy β N-terminal extension, which is especially abundant in prolines, can interact specifically and directly with SH3 domains of tyrosine kinases Fyn and CSK, phospholipase Cγ, NADPH oxidase activator 1 – p67phox, and cytoskeleton protein spectrin. Furthermore, C-terminal SH3 domain of p67phox can also interact with SH3 binding site that resides on the shared part of CoASyβ and CoASyα . These data demonstrated that CoA Synthases could be involved in complexes with signaling proteins in living cells which may regulate enzymatic activities of CoA Synthases or vice versa CoA Synthase may modulate some steps in signal transduction in the cell in currently unknown way.